Leaderships Style, Organization Culture on the Organizational Job Satisfaction in Improving Employee’s Perfomance. A Study at The Center for Plant Conservation at the Bogor Botanical Garden. - Munafis, Subhan; Djamil, Masyhudzulhak; Walujadi, Dedi (Jurnal Manajemen, 2018)
The study conducted at The Center for Plant Conservation Bogor Botanical Garden, which is the center for botanical research under the Indonesian Institute of Science (LIPI). Sampling method used is Incidental Sampling Methods. The number of respondence in this study were 90 respondents, all of them were employees of The Center for Plant Conservation Bogor Botanical Garden. Data were analyzed using the Path Analysis with computer program of IBM SPSS Statistics Version 22. The result of this research has shown that leadership style has positive effect (influence) on Job satisfaction. Job satisfaction has positive effect on employee’s performance. Leadership style has positive effect on employee’s performance. Organization culture has negative effect on job satisfaction and employee’s performance. Job satisfaction has contributes positively on employee’s performance.